Protocol for a prospective observational diagnostic study: intraoperative simultaneous limb pressure monitoring (INSTANT) study. Issue 8 (22nd August 2019) - Rockley, Mark; Jetty, Prasad; Wells, George A
Abstract : Introduction: Peripheral vascular disease (PVD) is a condition caused by arterial blockages causing inadequate blood flow, resulting in pain and gangrene of the legs. Endovascular therapy, such as angioplasty, can be used to treat PVD, however, the operator feedback during surgery is primarily anatomic based on the angiogram. Because physiologic blood perfusion can be difficult to determine based on anatomic images, we propose introducing physiological measurements into the operating room. This study will investigate whether the change in intraoperative monitoring of haemodynamic measurements such as the Toe-Brachial Index during endovascular surgery for lower extremity atherosclerotic PVD is associated with clinical outcomes such as major adverse limb events (MALEs). Methods and analysis: This study will be a prospective, operator-blinded and blinded endpoint adjudicated observational diagnostic cohort study. A total of 80 legs will be enrolled in the study. Ankle and toe blood pressures will be measured non-invasively at predetermined time points before, during and after surgery, and we will assess associations between changes in intraoperative pressure measurements and postoperative clinical and haemodynamic outcomes. The primary outcome will be MALE within 1 year, and secondary outcomes include follow-up pressure measurements, vessel patency, reintervention, clinical staging improvement, amputation and death. Ethics and dissemination: Regional hospital ethics approval has been granted (Ottawa Hospital Research Institute - Research Ethics Board, Protocol 20180656–01H). On completion of data analysis, the study will submitted for presentation at international vascular surgical society meetings, in addition to submission for publication in publicly accessible medical journals. Trial registration number: NCT03875846